2021
DOI: 10.1186/s12877-021-02385-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social network change and health decline: a qualitative study on experiences of older adults who are ageing in place

Abstract: Background Older adults prefer to age in place. Social network change and health decline challenge ageing in place, as stressors that make age-related advantages disappear. The aim of this study was to explore social network change and health decline and its impact on older adults who are ageing in place. Method In-depth interviews (n = 16) were conducted with older adults who were ageing in place and who were experiencing health decline and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…Of the 34 qualitative studies (Supplementary Figure S1 ), 24 were rated as low risk of bias [ 28 , 35 , 38 , 40 , 41 , 43 , 45 , 48 , 49 , 53 , 55 , 56 , 64 , 71 , 73 76 , 79 , 92 , 99 , 107 , 114 , 115 ], nine as moderate risk of bias [ 37 , 42 , 44 , 47 , 54 , 63 , 72 , 77 , 108 ] and one as high risk of bias [ 46 ]. Of the 83 quantitative studies (Supplementary Figure S2 - S3 ), 18 were rated as low risk of bias [ 3 , 62 , 70 , 80 , 86 , 89 , 96 , 105 , 113 , 116 125 ], 56 as moderate risk of bias [ 7 , 30 , 31 , 33 , 34 , 39 , 51 , 57 – 60 , 66 69 , 81 84 , 87 , 88 , 90 , 93 , 94 , 97 , 98 , …”
Section: Resultsmentioning
confidence: 99%
“…Of the 34 qualitative studies (Supplementary Figure S1 ), 24 were rated as low risk of bias [ 28 , 35 , 38 , 40 , 41 , 43 , 45 , 48 , 49 , 53 , 55 , 56 , 64 , 71 , 73 76 , 79 , 92 , 99 , 107 , 114 , 115 ], nine as moderate risk of bias [ 37 , 42 , 44 , 47 , 54 , 63 , 72 , 77 , 108 ] and one as high risk of bias [ 46 ]. Of the 83 quantitative studies (Supplementary Figure S2 - S3 ), 18 were rated as low risk of bias [ 3 , 62 , 70 , 80 , 86 , 89 , 96 , 105 , 113 , 116 125 ], 56 as moderate risk of bias [ 7 , 30 , 31 , 33 , 34 , 39 , 51 , 57 – 60 , 66 69 , 81 84 , 87 , 88 , 90 , 93 , 94 , 97 , 98 , …”
Section: Resultsmentioning
confidence: 99%
“…The same is true in a region in the south of the Netherlands where participants described themselves as social and hospitable. Respondents to this study mentioned that they liked to go out and were willing to continue their social participation [33]. Also, an age-friendly programme entitled "Ambition for Aging" (AfA) based in the North-West of England has shown that facilitating age-friendly work requires the presence of certain capitals in a neighborhood.…”
Section: Social Participationmentioning
confidence: 98%